Formation of readiness of future special teachers for professional activity by means of coaching technology (Journal of Educational Sciences, 2023)
This article examines the readiness of future special teachers for professional activity by means ofcoaching technology. Special attention is paid to innovative processes in the field of education and thepeculiarities of the innovation being introduced, as well as to the innovative development in potentialenvironment of the teaching staff at university. The innovation in this article is “coaching”, which createsconditions for the formation of an activity subject capable of realizing his professional potential. Coachingtechnology is a method of counseling and training during which helps a student to achieve a clearlydefined professional and life goal. In other words, coaching in the learning process helps the student toachieve the desired result. Therefore, the use of coaching technology at the present stage is relevant inthe training of special teachers. In scientific work, coaching is a unique technique created at the intersectionof philosophy, psychology, management and logic, used to increase the effectiveness and disclosureof a person’s potential, to solve his business and personal problems. The elements of the content of innovativemethods and forms of teaching are analyzed, the use of which will make the process of formingthe readiness of future special teachers purposeful and more effective. One of the stages of the study wasthe primary psychological and pedagogical diagnostics with the use of coaching technology. 72 studentsof Auezov South Kazakhstan University were surveyed. The elements of the content of innovative methods and formsof education are analyzed, the use of which will make the process of forming the readiness of future special teacherspurposeful and more effective.Key words: coaching, coaching technology, innovative technology, special teachers, readiness ofspecial teachers.